A Conferência de Minneapolis de 1888 e a Teologia da recepção: uma leitura histórico-teológica = Alternativtitel: The 1888 Minneapolis Conference and Reception theology : a historical-theological Reading - Ferreira, Reuberson Rodrigues (Plura, revista de estudos de religião, 2025)
This article analyzes the reception of the 1888 Minneapolis Conference within the Seventh-day Adventist Church in light of Reception Theology. It assumes that the message of justification by faith presented by Waggoner and Jones, with the support of Ellen White, initiated a dynamic process of theological appropriation. Drawing on thinkers such as Congar, Brighenti, and Thillard, the study identifies four stages in this reception: initial tension, silencing, rediscovery, and pluralism. It concludes that the reception of the 1888 message remains ongoing, challenging the Church to a renewed experience of Christ's righteousness.